2021
DOI: 10.3390/ijerph182412932
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Effects of Visual Stimulation with Green Plant Types

Abstract: This study was designed to assess the physiological and psychological benefits of visually looking at foliage plants in adults. This study involved 30 adults in their 20s (11 males, 19 females), and using a crossover design, participants looked at four different types of visual stimuli, namely, real plants, artificial plants, a photograph of plants, and no plants for 5 min. Brain waves were measured while viewing each type of plant, and a subjective evaluation of emotions was performed after each visual stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…One possible explanation is that the visualization technique may require training, since not all people have the capacity for imagination or inventiveness. These training periods will be longer for people with more problems, in whom all the senses must be stimulated to create a visualization that is as real as possible [ 40 ]. In this academic-year analysis, the authors focused on seeing anxiety and did not analyze whether there were students who had problems imagining a system to reduce their stress or anxiety, and perhaps this meant that we did not generate significant data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation is that the visualization technique may require training, since not all people have the capacity for imagination or inventiveness. These training periods will be longer for people with more problems, in whom all the senses must be stimulated to create a visualization that is as real as possible [ 40 ]. In this academic-year analysis, the authors focused on seeing anxiety and did not analyze whether there were students who had problems imagining a system to reduce their stress or anxiety, and perhaps this meant that we did not generate significant data.…”
Section: Discussionmentioning
confidence: 99%
“…One of the situations that generates the most stress and anxiety is not knowing what is going to happen. The purpose of visualization is to imagine a more comfortable situation so that when the real situation arrives, it can be faced with more security [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference between real and artificial leaves was in a physiological calm and relaxing sense when touching the real plants. Jeong and Park (2021) experiment looked at 4 kinds of visual stimuli which were the real plants, the artificial plants, the plant's picture, and no plants at all; revealed that the real plants give the most relaxing, comfortable, and natural score; which meant positive mood conditions. That's why natural plants are needed as an important element for the human environment.…”
Section: Qualitative Variablesmentioning
confidence: 99%
“…Mindfulness-based stress reduction (MBSR) training conducted in a natural outdoor setting leads to better mental health and well-being than the same training conducted indoors. 10 Viewing indoor plants can also have positive effects, such as higher scores for "comfort", "naturalness", "relaxation", increased positive mood 11 , or decreased feelings of stress. 12 However, not only viewing real plants can result in positive reactions.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, not only viewing real plants can result in positive reactions. Viewing artificial plants 11 or images depicting natural sceneries [12][13][14] is associated with greater well-being. 11 When viewing landscape images, participants sometimes felt more natural, relaxed, and at ease and had lower anxiety scores than after viewing images depicting urban scenes.…”
Section: Introductionmentioning
confidence: 99%